LPS Structure and PhoQ Activity Are Important for Salmonella Typhimurium Virulence in the Gallleria mellonella Infection Model - Bender, Jennifer K. (Public Library of Science, 2013)
The larvae of the wax moth, Galleria  mellonella , have been used experimentally to host a range of bacterial and fungal pathogens. In this study we evaluated the suitability of G . mellonella as an alternative animal model of Salmonella infection. Using a range of inoculum doses we established that the LD(50) of Salmonella Typhimurium strain NCTC 12023 was 3.6 × 10(3) bacteria per larva. Further, a set of isogenic mutant strains depleted of known virulence factors was tested to identify determinants essential for S . Typhimurium pathogenesis. Mutants depleted of one or both of the type III secretion systems encoded by Salmonella Pathogenicity Islands 1 and 2 showed no virulence defect. In contrast, we observed reduced pathogenic potential of a phoQ mutant indicating an important role for the PhoPQ two-component signal transduction system. Lipopolysaccharide (LPS) structure was also shown to influence Salmonella virulence in G . mellonella . A waaL (rfaL) mutant, which lacks the entire O-antigen (OAg), was virtually avirulent, while a wzz (ST)/wzz (fepE) double mutant expressing only a very short OAg was highly attenuated for virulence. Furthermore, shortly after infection both LPS mutant strains showed decreased replication when compared to the wild type in a flow cytometry-based competitive index assay. In this study we successfully established a G . mellonella model of S . Typhimurium infection. By identifying PhoQ and LPS OAg length as key determinants of virulence in the wax moth larvae we proved that there is an overlap between this and other animal model systems, thus confirming that the G . mellonella infection model is suitable for assessing aspects of Salmonella virulence function.